Abraham Lincoln papers - Lincoln, Abraham, 1809-1865.
Correspondence, speeches, and articles. Includes letters received by William H. Herndon, Lincoln's law partner and biographer, regarding Lincoln.
Microfilm of originals in the Henry E. Huntington Library, San Marino, Calif.
Henry E. Huntington Library
U.S. president and representative, abolitionist, lawyer, and state legislator from Illinois.
Keywords: Herndon, William Henry, -- 1818-1891 -- Correspondence; Presidents -- United States